Investigating the cyclic breaking of butyl-, methyl- and ethyl-biodiesel from waste vegetable oil using ultraviolet-visible spectrophotometry. Issue 1 (1st January 2017) - Emetere, M.E.; Aro, I.S.; Jack-Quincy, S.; Okonkwo, O.D.; Ojewumi, M.E.; Omodara, O.J.; Jasper, E.N.; Adeyemi, A.O.
Abstract: The main advantage of biodiesel to fossil-diesel is attributed to the ester functional group in its structure. Many researchers have affirmed that the functional group assists the diesel engine to function at its peak. However, the efficiency of the biodiesel to keep the mechanical piston-strokes in the diesel engine is experimentally presumed low especially if the engine works for a long time. In this research, it was proposed that the cyclic break down of the ester functional group of biodiesel is a major disadvantage. Butanol, ethanol and methanol biodiesel were produced in the laboratory using waste vegetable oil from restaurant. The Ultraviolet-visible spectroscopy or spectrophotometer (UV–Vis) was used to investigate the cyclic break down in the Butyl-, Methyl- and Ethyl- biodiesel. The Ultraviolet-visible spectroscopy or spectrophotometer (UV–Vis) was used to probe the various biodiesel samples with a start and stop wavelength of 500 and 900 nm respectively. The wavelength interval was 1 nm at a high scanning speed. Between 500–550 and 800–850 nm, the Ethyl- and Butyl- biodiesel had an absorbance of 2.7 and 1.6 respectively with 3 peaks each. Methyl-biodiesel had the highest absorbance of 1.7 at 600–650 nm with 1 peak. The computational extrapolation of all outcomes affirms that cyclic breaking is highest in Butyl-biodiesel. The most resilient biodiesel type was the Ethyl-biodiesel. However, it was recommended that cyclic breaking may be preserved by ratio-mixing of biodiesel with fossil-diesel.